The impact of depot medroxyprogesterone acetate on fracture risk: a case-control study from the UK. Issue 1 (January 2017) - Kyvernitakis, I.; Kostev, K.; Nassour, T.; Thomasius, F.; Hadji, P.
Abstract Summary There has been concerning about women receiving depot medroxyprogesterone acetate (DMPA) contraception because of the prolonged hypoestrogenemic state regarding the potential negative effects on bone health. This study showed that DMPA exposure is associated with increased fracture risk and that fracture risk increases with longer DMPA exposure. Introduction DMPA has been associated with impaired bone mineral acquisition during adolescence and accelerated bone loss in later life. We performed this large population-based study to assess the association between use of DMPA or combined oral contraceptives and the incident risk of fracture. Methods We identified 4189 women between 20 and 44 years of age with a first-time fracture diagnosis, matched them with 4189 random controls using the Disease Analyzer database and investigated the relation with DMPA exposure. Results Overall, 11 % of the fracture cases and 7.7 % of the controls had DMPA use recorded. The adjusted OR for developing a fracture in patients with current use of DMPA compared to non-users was 0.97 (95 % CI 0.51–1.86), 2.41 (95 % CI 1.42–4.08), and 1.46 (95 % CI 0.96–2.23) for 1–2, 3–9, and ≥10 prescriptions, respectively. The adjusted OR for developing a fracture in patients with past use of DMPA compared to non-users was 0.96 (95 % CI 0.73–1.26), 1.14 (95 % CI 0.86–1.51), and 1.55 (95 % CI 1.07–2.27) for 1–2, 3–9, and ≥10 prescriptions, respectively. The highest fracture risk was identified in young patients less than 30 years with longer DMPA exposure (≥10 prescriptions; OR 3.04, 95 % CI 1.36–6.81), as well as in patients in the late reproductive years with past use of DMPA (OR 1.72, 95 % CI 1.13–2.63). Conclusions Our results indicate that DMPA exposure is associated with increased fracture risk and may have negative effects on bone metabolism, resulting in impaired bone mineral acquisition during adolescence and accelerated bone loss in adult life.